2022
DOI: 10.4149/bll_2022_120
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against COVID-19 as prevention of occupational disease in University of Defence members in the Czech Republic - motivation for vaccination and reasons for hesitancy

Abstract: OBJECTIVES: The aim of this cross-sectional study was to investigate the determinants of COVID-19 vaccine acceptance in University of Defence members. BACKGROUND: Vaccination is the most important method of prevention against COVID-19 and achieving suffi cient vaccination rate is thus essential to maintain the military capability. METHODOLOGY: An online questionnaire was distributed electronically to 2,408 respondents in autumn 2021. The survey was designed to collect demographic predictors of vaccination, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…When choosing a vaccine, men were more likely than women made their decision based on information about the effectiveness of a given vaccine provided in the media (30.3% vs. 24.8%). In a study by Kupsova et al, it was found that women more often than men claimed the desire to protect their health was the reason for vaccination against COVID-19 (80.8% vs. 72.1%), while the possibility of avoiding tests for SARS-CoV-2 was less frequently reported by women (28.1% vs. 41.5%) [5].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When choosing a vaccine, men were more likely than women made their decision based on information about the effectiveness of a given vaccine provided in the media (30.3% vs. 24.8%). In a study by Kupsova et al, it was found that women more often than men claimed the desire to protect their health was the reason for vaccination against COVID-19 (80.8% vs. 72.1%), while the possibility of avoiding tests for SARS-CoV-2 was less frequently reported by women (28.1% vs. 41.5%) [5].…”
Section: Discussionmentioning
confidence: 98%
“…Med Pr Work Health Saf. 2024;75 (2) of the vaccine (68.7%) and having no fear of COVID-19 (64.2%) [5].…”
Section: Discussionmentioning
confidence: 99%